2016
DOI: 10.3390/s16040540
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep Deprivation Induces a Local Brain Transfer Information Increase in the Frontal Cortex in a Widespread Decrease Context

Abstract: Sleep deprivation (SD) has adverse effects on mental and physical health, affecting the cognitive abilities and emotional states. Specifically, cognitive functions and alertness are known to decrease after SD. The aim of this work was to identify the directional information transfer after SD on scalp EEG signals using transfer entropy (TE). Using a robust methodology based on EEG recordings of 18 volunteers deprived from sleep for 36 h, TE and spectral analysis were performed to characterize EEG data acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…The impairment upon this adaptive decoupling further impacts SD vulnerability and induces ambiguity in sleep/wake stages definitions (Krause et al, 2017). In line with these data, short-range increases were obtained for the frontal areas after SD with increased connectivity and lower global integration (Alonso et al, 2016).…”
Section: Sleep Loss Violence and Functional Brain Networksupporting
confidence: 72%
“…The impairment upon this adaptive decoupling further impacts SD vulnerability and induces ambiguity in sleep/wake stages definitions (Krause et al, 2017). In line with these data, short-range increases were obtained for the frontal areas after SD with increased connectivity and lower global integration (Alonso et al, 2016).…”
Section: Sleep Loss Violence and Functional Brain Networksupporting
confidence: 72%
“…However, this effect was not observed after 28 h of TSD treatment. Alonso (2016) [ 82 ] recorded EEG during 36 h TSD in 18 healthy adults and found that although transfer entropy significantly decreased after 36 h TSD, the decrease in information transfer during sleep deprivation predominately started after 24 h of TSD.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is likely to be a compensatory activation response of neurons in the frontal lobe that is purposed to buffer changes in brain function caused by apnea/hypopnea. 1,38 The frontal cortex plays an important role in executive function, selective attention, and short-term memory maintenance. 39 During the events, sleep-dependent memory consolidation is also disrupted by frontal activation.…”
Section: Discussionmentioning
confidence: 99%